2014
DOI: 10.1080/13506285.2014.881445
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements in developing readers: A comparison of silent and oral sentence reading

Abstract: We present sentence reading data from a large-scale study with children (N = 632), focusing on three key research questions. (1) What are the trajectories of reading development in oral as compared to silent reading? (2) How are word frequency effects developing and are changes differentially affected by reading mode? (3) Are there systematic differences between better and weaker comprehenders when reading silently vs. aloud? Results illuminate a number of differences between reading modes, including more and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
80
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 58 publications
12
80
2
3
Order By: Relevance
“…The same has been found in previous studies with first, second and third graders (Buswell, 1922;McConkie et al, 1991;Taylor, 1965; for an overview, see Table 36.1 in Blythe & Joseph, 2011). Vorstius, Radach, and Lonigan (2014) reported a similar finding and described it as follows: "across all viewing time measure parameters the biggest gain appears to be happening between 1st and 2nd grade, whereas effects seem to level off between 4th and 5th grade" (p. 477). Like in other domains (Thorndike, 1913), learning proceeds along a decelerated function; it seems to be accelerated at the beginning of reading instruction and slows down with increased reading skill.…”
Section: Developmental Effectssupporting
confidence: 77%
“…The same has been found in previous studies with first, second and third graders (Buswell, 1922;McConkie et al, 1991;Taylor, 1965; for an overview, see Table 36.1 in Blythe & Joseph, 2011). Vorstius, Radach, and Lonigan (2014) reported a similar finding and described it as follows: "across all viewing time measure parameters the biggest gain appears to be happening between 1st and 2nd grade, whereas effects seem to level off between 4th and 5th grade" (p. 477). Like in other domains (Thorndike, 1913), learning proceeds along a decelerated function; it seems to be accelerated at the beginning of reading instruction and slows down with increased reading skill.…”
Section: Developmental Effectssupporting
confidence: 77%
“…Consistent with the findings of past eye‐tracking studies (Vorstius, Radach, & Lonigan, ), we observed differences in students’ global EM behavior as a function of grade level and passage difficulty. For the variables associated with lower level processing, younger students were more likely to have longer first‐fixation and gaze durations across passages as compared with the older students, suggesting that, as would be expected, younger students required more effort and time to decode the words.…”
Section: Discussionsupporting
confidence: 91%
“…Ashby, Yang, Evans, and Rayner (2012) for instance found that speech production in adults leads to lower rates of parafoveal processing in oral than in silent reading. The first large scale study of differences in oral and silent reading in children also suggests that reading aloud results in longer fixation durations, possibly due to speech and eye-voice coordination demands on working memory during reading (Vorstius, Radach, & Lonigan, 2014). The study also suggested that frequency effects may be attenuated in reading aloud compared to silent reading.…”
Section: Word Length and Frequency Effects In Children And Adultsmentioning
confidence: 95%
“…Findings are mixed and may reflect differences in participant ages and reading ability as well as the nature of reading materials used in these studies. In addition, as in all four studies participants read aloud, it is unclear whether findings generalize to children's silent reading (see Ashby, Yang, Evans, & Rayner, 2012;Vorstius, Radach, & Lonigan, 2014). To investigate this issue we present empirical evidence from a silent reading experiment and focus specifically on the interaction of word length and frequency effects http://dx.doi.org/10.1016/j.visres.2015.05.008 0042-6989/Ó 2015 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 95%